Developing a System for Graphical Analysis of Brainwaves During Media Consumption - Silva, Thiago Henrique Coelho Tavares da; Cavalcanti, Matheus Dantas; Marinho, Isaac Nóbrega; Becker, Valdecir (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
This paper describes a data visualization artifact, designed to capture, analyze and generate an imprint of the user’s brainwaves from electroencephalographic readings in realtime during the consumption of media content. Such waves, naturally emitted by the human brain, will be mapped, categorized, stored and graphically printed within the scope of the Design Science Research methodology. The generated Brain Computer Interface can be used as an input in various systems, such as neuromarketing and media recommendation. Given that experience and perception of media consumption is variable and, therefore, subjective among individuals, this research aims to obtain relevant data in the context of studying multimedia interaction and development.